Why does tourism have to confront the emissions trading scheme? Evidence from China. (October 2021) - Zhang, Jiekuan; Zhang, Yan
Abstract: This article examines the impact of ETS on tourism to demonstrate why tourism has to confront the emissions trading scheme (ETS), a world's leading climate policy. For this purpose, the current paper estimates the economic and environmental impacts of ETS on China's tourism and the underlying influence mechanism. The methodology draws on a time-varying difference-in-differences method combined with the propensity score matching technique based on Chinese provincial regions' panel data between 2005 and 2019. The results show that the Chinese ETS significantly reduces tourism-related carbon emissions and carbon intensity as well as contains tourism economic growth. Moreover, such effects increase gradually since the policy implementation in 2013. Moreover, the price significantly mediates ETS's influence on the economy, and the energy consumption structure significantly mediates ETS's influence on carbon emissions. The impact of ETS on tourism also varies considerably across different regions with various levels of economy, tourism, energy and industry. Highlights: This study answers how the emissions trading scheme affects tourism. This study employs a time-varying PSM- difference-in-differences approach. ETS significantly reduce tourism economic growth and its related carbon emissions. The price and energy consumption structure constitute the influence mechanism. ETS's effects on tourism vary across different regions with various economic traits.